Impact of Religion on Students’ Performance: A Study Among Muslim Students in District Bahawalpur - Nusrat Nawaz Abbasi; Shahzad Rasool; Muhammad Sami-ur-Rehman; Riffat Tahira (Journal of Management Practices, Humanities and Social Sciences, 2023)
This research study was designed to investigate the impact of religion on students’ performance: a study among Muslim students. The population of the study was secondary school students in District Bahawalpur. Multistage sampling technique was used to select the sample. Total of 480 secondary school students were included in the study. Researchers adopted Comprehensive Measure of Islamic Religion (CMIR) to measure the Islamic religion of Muslim students. A self-developed questionnaire was used to measure the student’s performance at the secondary level. Religion was further divided into two subscales. 1. Religious belief and 2. Religious practice. The Significant findings of this study were: Students strongly believe in their religion and follow their religious rules. They avoid sin and do well. It was also observed that they prayed to GOD for help and ideal students maintain a balance between curriculum and co-curriculum activities. This research will open avenue for scholars and as well practioners from the religious point of view.